STUDY OF PROGRESSIVE CHANGES IN BACTERIOLOGICAL CONSTITUENT OF HARVESTED RAINWATER FROM OYOKO COMMUNITY IN KUMASI, GHANA - Yeboah, Joy O.; Kodom, Kingsley (IJRDO-Journal of Applied Science, 2016)
he bacteriological characteristics of rainwater harvested from a typical rooftopwere progressively studied for a period of nine (9) months. The study area, Oyoko, is a ruralcommunity considered as a typical farming area and located about 30 km from Kumasi, thecapital city of Ashanti Region of Ghana. The collected rainwater samples were analyzed forEscherichia coli (E. coli) and salmonella. The entire E. coli counts varied from 0-60 CFU/100ml and were absent on 39 observations out of total of 84 observations (replicate samples),representing 46.4%. Whiles the entire salmonella counts ranged from 0-78 CFU/100ml andonly 10 observations out of the 84 were absent, which represents 11.9%. Both E. coli andsalmonella showed higher concentration during early stages of continuous rainfall but,progressively reduced during later part of rainfall. The main cause of this phenomenon can beattributed to the deposition and accumulation of pollutant materials on the rooftop andcatchment areas typically during the dry seasons as a result of wind-blown dirt particles andother environmental pollutants. The high bacteriological constituents in the early-stageharvested rainwater consequently have some proven significant health implications from theirdirect consumption. It is therefore imperative for the community to know the best time intervalto harvest their rainwater as rainfall progresses, and also know any health implicationsassociated with the harvested rainwater that goes into their storage tanks for consumptionthrough progressive monitoring of the quality.